Dose-Dependent Effects of Randomized Intraduodenal Whey-Protein Loads on Glucose, Gut Hormone, and Amino Acid Concentrations in Healthy Older and Younger Men - Giezenaar C; Luscombe-Marsh ND; Hutchison AT; Standfield S; Feinle-Bisset C; Horowitz M; Chapman I; Soenen S (MDPI (Basel, Switzerland))
Protein-rich supplements are used widely for the prevention and management of malnutrition in older people. We have reported that healthy older, compared to younger, adults have less suppression of energy intake by whey-protein-effects on appetite-related hormones are unknown. The objective was to determine the effects of intraduodenally administered whey-protein on glucose, gut hormone, and amino acid concentrations, and their relation to subsequent ad libitum energy intake at a buffet meal, in healthy older and younger men. Hydrolyzed whey-protein (30 kcal, 90 kcal, and 180 kcal) and a saline control (~0 kcal) were infused intraduodenally for 60 min in 10 younger (19-29 years, 73 ± 2 kg, 22 ± 1 kg/m²) and 10 older (68-81 years, 79 ± 2 kg, 26 ± 1 kg/m²) healthy men in a randomized, double-blind fashion. Plasma insulin, glucagon, gastric inhibitory peptide (GIP), glucagon-like peptide-1 (GLP-1), peptide tyrosine-tyrosine (PYY), and amino acid concentrations, but not blood glucose, increased, while ghrelin decreased during the whey-protein infusions. Plasma GIP concentrations were greater in older than younger men. Energy intake correlated positively with plasma ghrelin and negatively with insulin, glucagon, GIP, GLP-1, PYY, and amino acids concentrations (p < 0.05). In conclusion, intraduodenal whey-protein infusions resulted in increased GIP and comparable ghrelin, insulin, glucagon, GIP, GLP-1, PYY, and amino acid responses in healthy older and younger men, which correlated to subsequent energy intake.
Keywords: ageing; whey protein; gut hormones; 0908 Food Sciences; 1111 Nutrition and Dietetics